Meningitis and Encephalitis Management and Prevention Challenges (Springer International Publishing, 2018)
This book seeks to improve outcomes for meningitis and encephalitis cases handled by physicians who may or may not be thoroughly trained for these challenges. The text introduces the current guidelines but also discusses the gaps that leave clinicians struggling to implement the most appropriate approaches for these particular neurological infections. Each chapter delivers the tools necessary to identify and adhere to the most appropriate diagnostic technique, management protocols, and prevention approach for each situation. All chapters conclude with discourse on future directions in research and quality improvement. Written by experts in infectious diseases, the book covers topics that are the most devastating, including healthcare-acquired infections, autoimmune encephalitis, and infections as they present in HIV patients. Meningitis and Encephalitis is a well-rounded resource for all medical professionals encountering these neurological syndromes, including infectious disease specialists, neurologists, primary care physicians, and immunologists. .